Effects of Jian Pi Qing Chang Hua Shi decoction on mucosal injuries in a 2,4,6-trinitrobenzene sulphonic acid-induced inflammatory bowel disease rat model - Huicun Zhang; Na Ta; Hong Shen; Hongbing Wang (Taylor & Francis Group, 2021)
Context Jian Pi Qing Chang Hua Shi decoction (JPQCHSD) has been considered as an effective remedy for the treatment of inflammatory bowel disease (IBD) in Chinese traditional medicine. Objective We evaluated the efficacy of JPQCHSD on 2-4-6-trinitrobenzene sulphonic acid (TNBS)-induced IBD rats and the responsible mechanisms. Materials and methods Except the rats of the control group (50% ethanol), Sprague-Dawley rats (180 ± 20 g) induced by TNBS (150 mg/kg in 50% ethanol), received water extract of JPQCHSD daily at 0, 9.5, 19, or 38 g/kg for 12 days. The rats were sacrificed, and their colons were removed to evaluate the disease activity index. Malondialdehyde (MDA), superoxide dismutase (SOD), myeloperoxidase (MPO), immunoglobulin A (IgA), tumour necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and nuclear factor-κB were evaluated. Results JPQCHSD extract significantly reduced the disease activity index of TNBS-induced colitis with a median effective dose (ED50) of 26.93 g/kg. MPO and MDA were significantly reduced in the 19 and 38 g/kg groups (ED50 values 37.38 and 53.2 g/kg, respectively). The ED50 values for the increased SOD and IgA were 48.98 and 56.3 g/kg. ED50 values for inhibition of TNF-α, IL-1β, and IL-6 were 32.66, 75.72, and 162.06 g/kg, respectively. Discussion JPQCHSD promoted mucosal healing in IBD rats via its anti-inflammation, immune regulation, and antioxidation properties. Conclusions JPQCHSD has healing function on IBD. Further clinical trials are needed to demonstrate its efficacy and tolerance to IBD.